2002
DOI: 10.1074/jbc.m209493200
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modification of Epithelial Fatty Acid-binding Protein by 4-Hydroxynonenal in Vitro and in Vivo

Abstract: 4-Hydroxynonenal (4-HNE) is a cytotoxic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 49 publications
6
114
0
1
Order By: Relevance
“…4-HNE can bind to cysteine, histidine, and lysine residues of proteins via Michael addition reaction (Bennaars-Eiden et al, 2002;Macpherson et al, 2007). Thus, 4-HNE can increase oxidative post translational modification (PTM) and then alter protein function and cell signaling (Jin and Zangar, 2009;Ryan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…4-HNE can bind to cysteine, histidine, and lysine residues of proteins via Michael addition reaction (Bennaars-Eiden et al, 2002;Macpherson et al, 2007). Thus, 4-HNE can increase oxidative post translational modification (PTM) and then alter protein function and cell signaling (Jin and Zangar, 2009;Ryan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The HNE-modified proteins were identified as Hsp72 (inducible form of Hsp70), Hsp90, and protein disulfide isomerase (PDI) by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-MS) and liquid chromatography with electrospray ionization (ESI) tandem MS (LC-MS/MS) (15)(16)(17). Additionally, the same antibody was used to identify the epithelial fatty acid binding protein (E-FABP) as a site of HNE adduction in rat retinal homogenates (20). The identifications of HNE-adducted protein in the above-mentioned studies are limited because only HNE adducts on cysteine were detectable with the antibody used.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the 4-hydroxyacids are degraded by two parallel pathways. The first pathway, which involves 4-hydroxy-4-phosphoacyl-CoAs (4-Pacyl-CoAs), 3 leads to the formation of 3-hydroxyacyl-CoAs, which are physiological ␤-oxidation intermediates. The second pathway is a sequence of ␤-oxidation, ␣-oxidation (20,21), and ␤-oxidation steps.…”
mentioning
confidence: 99%
“…Some unsaturated 4-hydroxyacids are derived from 4-hydroxynonenal and 4-hydroxyhexenal, which are products of lipid peroxidation (1). The metabolism of 4-hydroxynonenal has been extensively studied, especially its conjugation with glutathione (2), covalent modification of proteins (3,4), and conversion to 4-hydroxynonenoate, 4-hydroxynonanoate and 1,4-dihydroxynonene, as well as its role in inflammatory processes (1,(5)(6)(7)(8)(9)(10)(11). However, the catabolism of its carbon skeleton has not been unraveled.…”
mentioning
confidence: 99%